APPLICATION OF REAL OPTIONS METHOD â BINOMIAL LATTICE WITH LEARNING OPTIONS IN OPTIMIZING TIN MINING PROJECT OF PT XYZ - Yolanda Indriyani O., Helen
Indonesia is a country that has a significant role in supplying world tin raw materials. Based on the reference mineral prices released by the Ministry of Energy and Mineral Resources, tin price was fluctuating since the last five years. The uncertain tin price trend is one challenge faced by the manager in the process of valuing the economic feasibility of a mining project. Therefore, an appropriate valuation method is needed so that Indonesia’s tin reserves can be optimized.